Usage habits of business information system in Hungary - Peter Sasvari (International Journal of Engineering and Innovative Technology, 2013)
The IT functions of the companies can be executed in different ways in-house solution, outsourcing, in sourcing,formation a spin-off company. Predominantly this function is provided within the company in Hungary. The larger a company is; it is more likely that a separate IT manager will be entrusted for the supervision of IT functions. Only a very small number of small-sized enterprises said that they paid special attention to formulating an IT strategy, while it was not considered important by microenterprises at all.
Keywords: M13; M15; 330; Business Information Systems; Hungary; Micro-; Small and Medium-Sized Enterprises